Rapprochement of the Positions of the EAEU Member States on the Issues of the Climate Agenda and Carbon Regulation - T. E. Migaleva; G. V. Podbiralina; L. L. Razumnova (Евразийская интеграция: экономика, право, политика, 2022)
Aim. Analyze the existing production potential in the EAEU countries and identify conditions for the development of a common climate policy and common mechanisms for carbon regulation based on the convergence of the positions of the member states of the integration association.Tasks. Determine the degree of use of the production potential of the EAEU; assess the possibilities and formulate proposals for enhancing the actions of the participating countries for its implementation in the field of sustainable development and climate policy.Methods. Based on the use of general scientific methods. In particular, the use of logical and comparative methods made it possible to most fully analyze the factors and trends of the processes under study; to identify problems that prevent convergence of the positions of the EAEU member states on the issues of the climate agenda and carbon regulation and propose possible options for their solution.Results. It has been determined that the existing production potential of the EAEU member countries is currently not fully realized. Its further development is associated with the need for investments to reload existing production capacities, technological renewal and an increase in labor productivity. Possible directions are presented that allow the EAEU countries to develop common positions on a unified climate policy and carbon regulation mechanisms.Conclusion. Today, climate problems are becoming irreversible and coming to the forefront of the international agenda, which is pushing countries to revise their carbon strategy. Based on the study, it was concluded that there are obstacles to the promotion of the “green” agenda in the EAEU, such as political and macroeconomic instability, the use of protectionist measures between the member countries of the association (this was especially characteristic during the pandemic), upholding their own sovereignty, etc.), which makes it difficult to develop joint mechanisms for regulating common markets. On the other hand, an assessment of the opportunities for convergence of the positions of the EAEU countries showed that there is a wide range of areas of interaction: for example, all EAEU countries have adopted national strategies for sustainable (“green”) development, which imply the modernization of economies through, including , and external financing, which creates incentives for the creation of joint companies and conditions for the development of a common climate policy and unified mechanisms for carbon regulation.